Intrinsic Motivation and Knowledge Investment Toward Interest Lecturer Invest in Indonesia Stock Exchange - Sugianto, La Ode; Ardiana, Titin Eka; Santoso, Slamet (AFRE (Accounting and Financial Review), 2019)
This study aims to add insight into investment and stock trading, as well as things that investors need to consider before investing. The approach used in research is quantitative explanatory research because the main purpose of this study is to prove the influence one variable on another. In this study the variables used are independent variables consisting of intrinsic motivation, and investment knowledge and the dependent variable, namely lectureâ€™s investment interest in the capital market. Data collection techniques in this study are using primary data that is questionnaire (questionnaire). The analytical method used in this study is to use multiple linear regression analysis. The results show that the influence of intrinsic motivation and investment knowledge simultaneously on the investment interests of lecturers at the Faculty Muhammadiyah Ponorogo University's economy with indicates pleasure, challenge, and satisfaction and type of investment, level of risk, and return.Â DOI: https://doi.org/10.26905/afr.v2i2.3726